Density functional theory investigation? ?for ?Au?_n, ?Au?_nLi ??(n=8,9) and Yn , YnCa (n=6,8) interactions - Maha Kassar (University of Thi-Qar Journal, 2022)
Geometry optimization for pure transition metals structures at B3LYP level, LaNL2DZ basis sets has been investigated by using Density Functional Theory (DFT) throughout Gaussian09 package. Electrostatic potential, contours, infrared spectra (IR) , HOMO LUMO energies, band gap, electronic energy, binding energy symmetry and density of states (DOS) have been achieved for all and . The energy gap for approximately equal to the energy gap of Gallium arsenide , this value of energy gap is in the range of values of band gaps of semiconductors, one can say like this sample of nanocluster play a vital rule in manufacturing of pieces of electronic devices such as transistors of processors in computers. The dipole moment of and are approximately zero values because they are homonuclear geometries, adding Lithium to Gold surfaces make the values of dipole moment increase dramatically, this distinct values results from they are hetronuclear structures, Diagrams of density of states give clear picture about the vacant orbitals that the electrons can occupy, one can visualize the interaction between gold surface and Lithium atom make the new structure possess the antiferromagnetic property, otherwise addition of Lithium atom to the Golden surface make it loses the antiferromagnetic property.